2020
DOI: 10.1155/2020/2918517
|View full text |Cite
|
Sign up to set email alerts
|

CD44, IL-33, and ST2 Gene Polymorphisms on Hepatocellular Carcinoma Susceptibility in the Chinese Population

Abstract: The interleukin- (IL-) 33/ST2 axis plays a pivotal role in tumorigenesis through influencing cancer stemness and other mechanisms. CD44 is one of the critical markers of hepatocellular carcinoma (HCC) among the cancer stem cells (CSCs). There is still a lack of CD44 gene single-nucleotide polymorphisms (SNPs) combined with IL-33/ST2 pathway single-nucleotide polymorphisms in HCC susceptibility analysis literature, although CD44 and IL-33/ST2 have been reported separately in human cancers. This study is aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Interestingly, two different polymorphisms in the IL-33 gene have been reported to increase the expression of IL-33 and to be associated with higher risk to develop hepatocellular carcinoma (Wei et al 2019b ; Pan et al 2020 ). Like other factors involved in stemness, IL-33 is also capable of inducing resistance to chemotherapy.…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, two different polymorphisms in the IL-33 gene have been reported to increase the expression of IL-33 and to be associated with higher risk to develop hepatocellular carcinoma (Wei et al 2019b ; Pan et al 2020 ). Like other factors involved in stemness, IL-33 is also capable of inducing resistance to chemotherapy.…”
Section: Main Textmentioning
confidence: 99%
“…Cluster of differentiation 44 (CD44) is a multifunctional transmembrane receptor expressed on various cell types, with ligand binding activating intracellular signalling pathways to stimulate cytokine release and lymphocyte activation [ 20 ]. The CD44 rs187115 T > C SNP is located within intron 1, with the C allele reportedly associated with a higher risk of HBV-HCC development in Taiwan and China [ 21 , 55 ]. The mechanisms are yet to be determined, but a role in the p53 stress response has been proposed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that IL-33 plays dual roles regulating tumor transformation, growth, and metastasis in many cancers, including non-small cell lung cancer (NSCLC), colorectal cancer, gastric cancer, pancreatic tumor, and breast cancer by directly acting on tumor cells or by indirectly affecting immune cells or the tumor microenvironment [ 219 , 220 , 221 , 222 , 223 , 224 ]. In some populations of China, individuals with at least one C allele of ST2 rs3821204 exhibited a higher risk of hepatocellular carcinoma compared to those with GG genes [ 225 ]. Patients with NSCLC in their peripheral blood exhibited increased IL-33 levels in serum and plasma, while IL-33 levels in plasma were decreased with disease progression [ 226 , 227 ].…”
Section: Il-33 and Immune-related Diseasesmentioning
confidence: 99%